Implementasi Internet of Things (IOT) untuk Monitoring dan Control Mesin Smokehouse di PT. Serena Harsa Utama - Hadiat Permadi; Ahmad Zaenul Irpan; Mikail Mambang Diawan; Sri Mulyeni (Merkurius : Jurnal Riset Sistem Informasi dan Teknik Informatika, 2025)
This study discusses the application of Internet of Things (IoT) technology in the monitoring and control system of smokehouse machines at PT Serena Harsa Utama. IoT enables the integration of sensors to monitor critical parameters such as temperature and humidity in real-time, thereby enhancing production efficiency and product quality. An experimental method was employed to test the effectiveness of the IoT system, with data collection through integrated sensors. The results indicate that IoT implementation can increase production efficiency by up to 30%, reduce human error, and optimize energy consumption. Despite challenges related to initial investment and operator training, the long-term benefits of IoT adoption, such as improved product quality and reduced downtime, make it a promising solution in the food processing industry. This research emphasizes the importance of adopting IoT technology to enhance competitiveness in the modern industry.